2004
DOI: 10.1002/gcc.20024
|View full text |Cite
|
Sign up to set email alerts
|

Gene amplification of atypical PKC‐binding PARD3 in radiation‐transformed neoplastic retinal pigment epithelial cell lines

Abstract: Neoplastic transformation induced by ionizing radiation was studied using a human retinal pigment epithelial cell line immortalized by telomerase. Radiation-transformed cell clones were tumorigenic in athymic mice and were analyzed by G-banding and comparative genomic hybridization (CGH). Radiation-transformed cloned cell lines and cell lines derived from tumors produced in athymic nude mice following transplantation exhibited a recurrent karyotype:45,XX,der(10),-13. CGH showed an amplification of 10p11.2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…29 In our work, we identified an overexpression of PAR-3 associated with an alteration of the localization of the protein both in the R-180 cell line and in the original tumor. Indeed, while PAR-3 was localized at the apical border of the cells in the proximal tubule of healthy kidney, as previously reported for epithelial cells, 30 PAR3 was observed as continuous and diffuse membranous staining and/or cytoplasmic in ccRCC.…”
Section: Discussionmentioning
confidence: 62%
“…29 In our work, we identified an overexpression of PAR-3 associated with an alteration of the localization of the protein both in the R-180 cell line and in the original tumor. Indeed, while PAR-3 was localized at the apical border of the cells in the proximal tubule of healthy kidney, as previously reported for epithelial cells, 30 PAR3 was observed as continuous and diffuse membranous staining and/or cytoplasmic in ccRCC.…”
Section: Discussionmentioning
confidence: 62%
“…For instance, TJs in MDCK cells exposed to ionizing irradiation were disassembled [60,61]. Recently, an interesting investigation by Zitzelsberger et al [62] showed that Par3 gene was strongly amplified in radiation-transformed retinal pigment epithelial cell lines, suggesting that Par3 may function in radiation-induced carcinogenesis. In addition, cellular response to ionizing radiation is cell shape-sensitive [63].…”
Section: Intercellular Junctions and Dna Damage Repairmentioning
confidence: 99%
“…A few studies have suggested an association of PARD3 with tumors (Fang and Xu, 2001;Zitzelsberger et al, 2004), and PARD3 was reported to be amplified in radiation-transformed neoplastic retinal pigment epithelial cell lines (Zitzelsberger et al, 2004). Also, various splicing transcripts of PARD3 are expressed in primary hepatocellular carcinomas, and the expression of exon 17b deleted PARD3 variants is downregulated in these carcinomas compared with the surrounding nontumorous liver tissues (Fang and Xu, 2001).…”
Section: Analysis Of Pard3 Defects In Primary Tumorsmentioning
confidence: 99%